The Natural Healing Companion : Using Alternative Medicines : What to Buy, How to Take, and When to Combine for Best Results - Wiancek, Deborah A. Dr. (Emmaus Rodale, 2000)
Natural Healing Now more than ever, people are turning to nature's cures for maximum health and well-being. In The Natural Healing Companion , naturopathic doctor Deborah A. Wiancek provides in-depth information about the four major categories of natural therapies--herbs, vitamin and mineral supplements, homeopathy, and Chinese patent formulas--plus an A-to-Z encyclopedia of diseases and conditions with suggested remedies. You'll find: Hundreds of drug-free remedies for more than 230 diseases and conditions, from abscesses and acne to varicose veins and whooping cough. You'll see which natural remedies are recommended for each, and which can be used in combination for best results. Comprehensive descriptions of 128 healing herbs; 83 vitamins, minerals, and other supplements; 102 homeopathic remedies; and 79 Chinese medicines complete with recommended uses, dosages, cautions, and much more. These natural remedies are widely available in health food stores, pharmacies, and grocery stores. Practical advice on your number one health concerns, from diet, exercise, and weight loss to choosing multivitamins and reading labels. The most comprehensive resource of its kind, The Natural Healing Companion is the first to combine so many natural therapies into a single, easy-reference volume, broadening your options for treating health problems, preventing illness, and maintaining good health.
Include Index.
Keywords: Naturopathy -- Alternative Medicine